Pendampingan Pembelajaran Makhorijul Huruf Pada Siswa SDN 2 Klepu, Sawo, Ponorogo - Retnowati, May Shinta; Naufal, Muhammad Zaky; Sujatmiko, Muhammad (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Community service activities are training and mentoring in an effort to improve the performance of reading the Qur'an for students of SDN 02 Klepu. This assistance aims to keep oral from errors in reading the Quran, the lack of Quran reading skills possessed by SDN 02 Klepu students is targeted in this PPM activity. This is one of the most important problems because this institution is an institution based on Islamic values so that the skill of reading the Qur'an is a basic ability that must be possessed by students of SDN 2 Klepu Kec. Soko Kab. Ponorogo. This mentoring program was attended by around 46 students and students, while the implementation consisted of several stages on the concept of makarijul letters in reading the Qur'an. This assistance lasts for 3 days from April 4 to 6, 2023. The results of this service show that the ability to read the Quran possessed by SDN 02 Klepu students has increased.